Business process modelling using ontological task models - Burov, Y. (Commission of Motorization and Energetics in Agriculture, 2014)
Knowledge-based technologies form a basis for creation of flexible intelligent enterprise. Methods of business process modelling using ontological tasks models allow to create an active modelling system to capture and reuse knowledge patterns in form of ontological models while preserving overall consistency via common ontology usage. High-level business process ontology is presented. Models for business and decision making operations along with their representation in system are specified. Business process modelling tool using task models is described.
Keywords: ontology; business process; modelling; task model; intelligent enterprise